Induction of Neutralizing Antibodies to T-Cell Line-Adapted and Primary Human Immunodeficiency Virus Type 1 Isolates with a Prime-Boost Vaccine Regimen in Chimpanzees - Zolla-Pazner, Susan (American Society for Microbiology, 1998)
Five chimpanzees were immunized by administration of one or more intranasal priming doses of one to three recombinant adenoviruses containing a gp160 insert from human immunodeficiency virus type 1 (HIV-1) MN (HIV-1(MN)) followed by one or more boosts of recombinant HIV-1(SF2) gp120 delivered intramuscularly with MF59 adjuvant. This regimen resulted in humoral immune responses in three of five animals. Humoral responses included immunochemically active anti-HIV-1 antibodies (Abs) directed to recombinant gp120 and neutralizing Abs reactive with T-cell-line-adapted HIV-1(MN) and HIV-1(SF2). In addition, neutralizing activity was detected to the two homologous primary isolates and to two of three heterologous primary isolates which, like the immunizing strains, can use CXCR4 as a coreceptor for infection. The three animals with detectable neutralizing Abs and a fourth exhibiting the best cytotoxic T-lymphocyte response were protected from a low-dose intravenous challenge with a cell-free HIV-1(SF2) primary isolate administered 4 weeks after the last boost. Animals were rested for 46 weeks and then rechallenged, without a boost, with an eightfold-higher challenge dose of HIV-1(SF2). The three animals with persistent neutralizing Abs were again protected. These data show that a strong, long-lived protective Ab response can be induced with a prime-boost regimen in chimpanzees. The data suggest that in chimpanzees, the presence of neutralizing Abs correlates with protection for animals challenged intravenously with a high dose of a homologous strain of HIV-1, and they demonstrate for the first time the induction of neutralizing Abs to homologous and heterologous primary isolates.